Cervix Carcinoma: Pathological Aspect - Nefertiti, Eva Pravitasari (Universitas Hang Tuah, 2018)
Cervix carcinoma is a malignancy at squamocollumnar junction, in the border between ecto and endo cervix. Lesion at this site is frequently correlated with chronic inflammatory of the cervix, displacia, and in situ carcinoma. InIndonesia, cervix carcinoma is the most common malignancy in women. At Obstetry and Gynecology Department of RSCM during 1986-1990 period, 2360 gynocology carcinoma were found, and 1821 (77,2%) cases of them were cervix carcinoma. The diagnosis was made based on cytology, colposcopy, biopsy, endocervix curettage and conitation. Papanicolaou test is a useful in detecting early stage of cervix carcinoma up to 90% accuration. The speciment for paps smear is secrets of the vagina, cervix, endocervix, endometrium, and posterior fornix.key words : cervix carcinoma, cytology, papsmear